Prevalence Of Gastrointestinal Parasites In Bow Fees In Authorization Lambaro Subdistrict Ingin Jaya Districts Aceh Besar - Cut Lady Fitria; Iswadi Iswadi; Khairil Khairil; Safrida Safrida; Mudatsir Mudatsir (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2023)
Gastrointestinal parasites are parasites that can infectes the gastrointestinall tracted of both humany and animal. These parasited can life in all parts of the body, but most of their life cycle is in the intestine. If the parasite infects cows in large numbers it can cause intestinal damage and result in thickening of the intestinal walls, then the cattle will become infected with worms and will have diarrhea which will result in loss of body fluids and will end in death. This study aims to determine the types of gastrointestinal parasites and what is the prevalence of gastrointestinal parasites foundinh in cow feces at Lambaro RPH. The research sample was obtained at the Lambaro RPH, Want Jaya District, Aceh Besar District and was identified at the Biology FKIP Laboratory at Syiah Kuala University in August 2022. This research used the floating method. The data is processed and analyzed using the prevalence formula. The results showed that there were 7 types of gastrointestinal parasites consisting of Ascaris lumbricoides, Monezia sp, Capilaria sp, Taenia saginata, Paramphistomun sp, Toxocara vitulorum, Paragonium westermani and the category of prevalence of gastrointestinal parasites included in the category of frequently infected. The concllusion of research was that the prepare of gastrointestinal parasites was found to be 11% with the dominant species found being Ascaris lumbricoides and the lowest being Paragonium westermani.Keywords: prevalence, gastrointestinal parasites, faeces, cattleParasit gastrointestinal ialah parasit yang mampu menyerang saluran pencernaan terhadap manusia ataupun hewan. Parasit ini bisa tumbuh pada bagian tubuh keseluruhan, namun banyak factor hidup pada usus keberadaanya. Jika parasit menyerang sapi pada jumlah besar bisa menimbulkan kerusakan usus dan menimbulkan dinding-dinding usus menebal, serta ternak yang terserang cacing dan diare menimbulkan cairan tubuh berkurang dan pada akhirnya mati. Penelitian ini bertujuan untuk mengetahui jenis-jenis parasit gastrointestinal dan berapakah prevalensi parasit gastrointestinal yang ditemukan pada feses sapi di RPH Lambaro. Sampel penelitian di peroleh pada RPH Lambaro Kecamatan Ingin Jaya Kabupaten Aceh Besar dan di identifikasi dilakukan di Laboratorium FKIP Biologi Universitas Syiah Kuala pada Bulan Agustus 2022. Penelitian ini mengunakan metode apung. Data di olah dan di analisis mengunakan rumus prevelensi. Hasil penelitian menunjukkan bahwa ditemukan 7 jenis parasit gastrointestinal yang terdiri dari Ascaris lumbricoides, Monezia sp, Capilaria sp, Taenia saginata, Paramphistomun sp, Toxocara vitulorum, Paragonium westermani dan katagori prevelensi parasit gastrointestonal termasuk kedalam katagori sering terinfeksi. Kesimpulan dari penelitaian ini adalah prevalensi parasit gastrointestinal yang ditemukan 11 % dengan pesies yang dominan ditemukan adalah Ascaris lumbricoides dan terendah adalah Paragonium westermani Kata kunci: prevalensi, parasit gastrointestinal, feses, sapi